Criteria for Selecting Texts for Reading in a Foreign Language: Scientific Approaches and Modern Practices. - Mudra, Olena; Koropatnitska, Tetiana (Видавничий дім «Гельветика», 2025)
This article delves into the primary criteria for selecting reading materials in a foreign language. It offers an analysis of various scholars’ perspectives on the use of authentic texts and explores potential methods to optimize the text selection process. Emphasis is placed on the importance of both adapted and authentic texts in the context of language acquisition, while also acknowledging the pivotal role modern digital platforms play in this domain. The purpose of this study is to explore the role of text selection in foreign language teaching and its impact on achieving specific educational objectives, such as language acquisition, cultural understanding, and cognitive development. The selection of texts must be deliberate and align with both the linguistic needs of students and the pedagogical goals of the curriculum. A comprehensive review of scientific literature highlights key factors that influence the choice of texts, such as the learner’s proficiency level, the thematic relevance of the material, and the degree to which the content aligns with student motivation and interests. The article underscores how crucial it is for educational texts to be engaging, challenging, and appropriately tailored to the individual needs of the learner to maintain motivation and foster deeper learning. The combination of these factors plays a vital role in enhancing the overall effectiveness of foreign language instruction. Special focus is given to the transformative influence of digital technologies, particularly in the area of automated text selection. By leveraging advanced technological tools, educators are now able to streamline the selection process, ensuring that materials are not only linguistically suitable but also pedagogically relevant. The analysis of text selection in foreign language teaching is approached through several key factors: alignment with educational objectives, types of reading (global, selective, and detailed), psycholinguistic factors, technical considerations (multimedia and interactive resources), and linguistic and sociocultural contexts. The study also examines the distinction between authentic and adapted texts, as well as the role of digital platforms in providing access to diverse materials. The results indicate that text selection should be tailored to learners’ proficiency levels, interests, and motivations. The study highlights the importance of using authentic materials for advanced learners, while adapted texts are beneficial for beginners and intermediate students. The integration of multimedia resources and digital technologies provides more flexible learning opportunities, enhancing engagement and improving listening and speaking skills. Psycholinguistic factors, such as motivation and cognitive appropriateness, are crucial for the effectiveness of the selected materials. The selection of texts for foreign language teaching should take into account pedagogical and psychological considerations, ensuring that the materials are suitable for the learners’ proficiency level and personal interests. Adapting texts to the students’ needs and incorporating multimedia and digital resources can significantly improve the learning process. Authentic texts are essential for developing communicative competence and cultural understanding, fostering a deeper connection between language and culture. The article concludes with a set of recommendations aimed at refining the text selection process. These recommendations emphasize the importance of leveraging digital tools to offer dynamic, personalized, and effective language learning experiences. The overall goal is to ensure that learners are not only exposed to language content that aligns with their proficiency and interests but also engaged in a way that maximizes the impact of their language acquisition journey. In light of these advancements, the article advocates for an evolving, tech-enhanced approach to reading in foreign languages, one that fosters greater learner engagement and success.
КРИТЕРІЇ ВИБОРУ ТЕКСТІВ ДЛЯ ЧИТАННЯ ІНОЗЕМНОЮ МОВОЮ: НАУКОВІ ПІДХОДИ Й СУЧАСНІ ПРАКТИКИ
Keywords: text; text selection; foreign language learning; text accessibility; cognitive load; motivation; instructional design; communicative competence; cognitive processing; authentic materials; digital learning; LATILL